"Heroic" Asylum Seekers from Around the World: Creating a Future from a Traumatic Past. (19th July 2012) - Eisold, Barbara
ABSTRACT This paper describes a multi‐national group of political asylum seekers, designated as "heroes" because they seem to have chosen to resist, when instead they might simply have moved elsewhere. Inspection reveals that they are also chosen by their families to continue a tradition of resistance, which has existed across generations. Once it is their turn, they endure repeated incidents of torture at the hands of oppressors, until finally they are threatened with death. Then, unlike their predecessors, they change course entirely and flee. This action is accomplished with considerable help from their families. Unlike two other resister groups, who tended to remain in the resistor role until they reached victory or death, "heroic" asylum seekers relinquish the thrill of the fight and take flight, seemingly because of a family mandate to do so, in order to move the family elsewhere. An attempt is made to understand the complex motivation behind these acts from a psychoanalytic perspective. What happens once they arrive here, however, is hard to predict. Brief follow‐up data indicates that successful adjustment is not guaranteed and will depend on a set of strengths similar to those required of all immigrants. These include a solid early attachment history, past adult experiences which have been affirming, and considerable local group support. In addition, access to services for the survivors of torture can be useful, although referral to these is (shockingly) happenstance. Thus, despite the peaceful trend their arrival may represent, many forces must come together if its goal is to be achieved. Copyright © 2012 John Wiley & Sons, Ltd.